ANALISIS PEMECAHAN MASALAH MATEMATIKA MENURUT POLYA MATERI SISTEM PERSAMAAN LINIER DUA VARIABEL - Irawanti, Ida; Hariyani, Sri; Suwanti, Vivi (Prodi Pendidikan Matematika FKIP Universitas Madura, 2024)
This study focuses on discussing the result of the analysis of (1) the ability to solve mathematical problems of SPLDV material based on Polya, (2) the causes of student errors in solving mathematical problems of SPLDV material. This research is qualitive research and the type of research is qualitive-exploratory. The subject in this study were class X student of SMK Bina Kartika Nusantara Tirtoyudo. Data collection procedures observations, through tests, interviewers, and documentation. Data is analyzed qualitatively including data reduction, data presentations, and drawing conclusions. Checking the validity of the data is carried out by triangulation. The test results from this study show that there are 3 excellent criteria, there are 4 good criteria, there are 5 students , and The criteria are less than 3 students. The causes of student errors in this study are forgetting or not remembering formulas, difficulty understanding symbols that cause work and the final result is not just right. The conclusion of this study is that students with high categories are able to meet all indicators including understanding problems, planning solutions, implementing solutions and rechecking. Learners with a moderate category are only able to meet the indicators of understanding the problem, planning the solution and carrying out the solution. Learners with low categories are only able to understand the problem and plan for a solution.